Polish Immigrants and the Challenges of Political Incorporation in the Republic of Ireland. Issue 2 (2nd April 2016) - O'Boyle, Neil; Fanning, Bryan; Di Bucchianico, Viola
Abstract: Poles constitute the largest immigrant community in the Republic of Ireland and, according to the 2011 census, more than 2.5 per cent of its population. Polish has become the country's second most commonly spoken language. Notwithstanding efforts by immigrant organisations, most notably Forum Polonia, and efforts by Polish candidates to contest local government elections in 2009 and 2014, the current picture is one of chronic under-representation. Bloemraad's model of 'structured mobilisation' suggests two principal routes for immigrant political incorporation: (i) mobilisation via the ethnic community itself (ethnic organisations and community leaders) and (ii) mobilisation via mainstream actors (political parties). In respect of the first, we examine efforts by the Polish community in Ireland to mobilise voters and garner support for Polish candidates in the 2014 local elections. In respect of the second, we draw on 10 years of longitudinal research on responsiveness by Irish political parties to immigrants. 2014 witnessed a sharp decline in efforts by political parties to reach out to immigrants entitled to vote compared to 2009. This institutional response, we suggest, had much to do with justifiable perceptions that immigrants were unlikely to mobilise, register to vote in large numbers or exercise their franchise.